Сучасний стан досліджень і розробок у сфері технології термоелектричного генерування в Японії - Кадзікава, Т. (Термоелектрика, 2009)
Ця стаття – огляд сучасного стану досліджень і розробок термоелектричних систем генерування потужності і термоелектричних матеріалів у Японії. Стисло показано деякі наукові результати, що стосуються перспективних матеріалів, таких як шаруваті оксиди, низькорозмірні наноструктурні оксиди, напівгейслерові сполуки та ін., з огляду на екологічно безпечні матеріали і наноструктурну технологію. Дослідження нових термоелектричних матеріалів і систем рекуперації відпрацьованого тепла проведено Національним інститутом передової промислової науки і техніки в рамках майбутніх національних проектів. Данная статья представляет собой обзор современного состояния исследований и разработок термоэлектрических систем генерирования мощности и термоэлектрических материалов в Японии. Кратко представлены некоторые научные результаты, касающиеся перспективных материалов, таких как слоистые оксиды, низкоразмерные наноструктурные оксиды, полугейслеровы соединения и другие, с точки зрения экологически благоприятных материалов и наноструктурной технологии. Исследования новых термоэлектрических материалов и систем рекуперации отработанного тепла были проведены Национальным Институтом передовой промышленной науки и техники в рамках будущих национальных проектов. Thermoelectric technology, in particular, thermoelectric power generation technology, has been expected to play an important role in the environmental conservation, energy security and stimulus to industry in the future in Japan. The paper summarizes an overview of the present status of research and development on thermoelectric power generation systems and the related thermoelectric materials in Japan. The progressing development activities have been carried out by the project members of private companies after finishing 5-year national project for Advanced Thermoelectric Conversion Systems. The demonstration system experiments using practical heat sources such as a 500kW diesel engine cogeneration system and a 10 t/day sewage treatment plant have been achieved. In parallel with these experiments the small scale demonstration system experiments have been also carried out using the hot springs and the waste heat from motorcycle. The research on various kinds of thermoelectric materials has been energetically carried out by universities and national research institutes mainly. Several topics of scientific results on advanced materials such as layered oxides, low-dimensional nanostructured oxide, half-Heusler compound and so on from the view point of environmentally friendly materials and nanosturucture approach are briefly introduced. The investigation including innovative thermoelectric material research and waste heat recovery systems has been achieved as one of the forthcoming national projects by AIST (National Institute of Advanced Industrial Science and Technology).